Acute Myocardial Infarction Complicating Coronavirus Infection (Case Report) - L. A. Davydova; D. A. Ostapchenko; S. V. Tsarenko; A. I. Gutnikov; G. N. Arbolishvili; V. A. Kovzel (Общая реаниматология)
Coronavirus infection caused by the SARS-CoV-2 virus is a multifaceted disease due to generalized vascular endothelial damage. Endothelial damage also underlies COVID-associated coagulopathy.The paper presents a case of coagulopathy causing myocardial infarction in a 43-year-old patient with no history of coronary disease. We have reviewed the available literature for the pathophysiological rationale of the assumed possibility of coronary thrombosis resulting from coagulopathy with the intact intima of the coronary arteries.Conclusion. The present observation of coronary thrombosis with radiographically intact coronary artery intima confirms the important role of coronavirus infection in triggering endothelial dysfunction. Currently, the most effective strategy for this type of coronary lesions is the use of anticoagulants and antiplatelet agents along with ECG, echocardiography and troponin level monitoring.